This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Though this is not needed , but thought I should just mention it . A formula which might come in handy is Γ ( n + 2 1 ) = 2 n ( 2 n − 1 ) ! ! π
Input n = 2
Problem Loading...
Note Loading...
Set Loading...
Using the facts that n ! = n ( n − 1 ) ! and ( 2 − 1 ) ! = π , ( 2 3 ) ! = 2 3 × ( 2 1 ) ! = 4 3 × ( 2 − 1 ) ! = 4 3 π Calculus is required to prove any of these values, but briefly, the reason that ( 2 − 1 ) ! = π is that Γ ( n ) = ∫ 0 ∞ e − x x n − 1 d x ∫ − ∞ ∞ e − x 2 d x = π Before you ask, the lower limit of integration changed to negative infinity since it is an even function; after substitution, the integral contains a 2 which has been factored out.